2015
DOI: 10.1093/mnrasl/slv005
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evidence of GeV dark matter

Abstract: Recently, an excess of GeV gamma ray near the Galactic Centre has been reported. The spectrum obtained can be best fitted with the annihilation of 30 − 40 GeV dark matter particles through bb channel. In this letter, I show that this annihilation model can also solve the mysteries of heating source in x-ray plasma and the unexpected high gamma-ray luminosity. The cross section constrained by these observations give excellent agreements with both the predicted range by using Fermi-LAT data and the canonical the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…On the other hand, it can be shown that the annihilation of dark matter particles can also provide the required energy source of soft and hard components of hot plasma in the Galactic Centre. The predicted cross section is ⟨ V⟩ ≈ (2-6)× 10 −26 cm 3 s −1 [19]. All these results are generally consistent with each other and satisfy the constraints from cosmic microwave background and low-redshift data [20].…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, it can be shown that the annihilation of dark matter particles can also provide the required energy source of soft and hard components of hot plasma in the Galactic Centre. The predicted cross section is ⟨ V⟩ ≈ (2-6)× 10 −26 cm 3 s −1 [19]. All these results are generally consistent with each other and satisfy the constraints from cosmic microwave background and low-redshift data [20].…”
Section: Discussionsupporting
confidence: 83%
“…This work is further supported by a later study which includes consideration of foreground and background uncertainties (Calore et al 2015). On the other hand, Chan (2015) showed that this dark matter model can also explain the origin of hot gas near the Galactic center.…”
Section: Introductionsupporting
confidence: 63%